Situation Report: Hungary, 1 August 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Cautious Liberalization of Electoral Law Permitted / by Alfred Reisch Foreign Minister Puja Removed in Party-Government Reshuffle / by Alfred Reisch Hungary to Become France's Privileged Partner in Eastern Europe / by Alfred Reisch Popularity of the Hungarian Model / by Laszlo Rasko Decree to Preserve Lake Balaton / by Eva Lengyel The Pope in Poland: The Hungarian Coverage / by Eva Lengyel Jesus Christ Superstar Reaches Hungary / by Judith Pataki